TRANSPLANTASI OVARIUM DOMBA INTRAUTERIN PADA KELINCI LOKAL - Sumarmin, Ramadhan (Sainstek : Jurnal Sains dan Teknologi, 2010)
The research to describe the ewe ovarian status post transplanted intrauterine in local pseudo pregnant rabbit had been conducted by using a descriptive method in which the 4 pieces to 4 spaces of ewe ovarian were transplanted to each of the rabbit?s cornua uterine. The description of completed ovarian post the transplanted scored with 4 (90-100% completed), 3 (70-90% completed), 2 (50-70% completed) , and 1 (<50% completed). In the research, the COCs (Cumulus Oophorus Complexes) were collected by slicing method, and then the date of the CoCs was analyzed by ANOVA and DNMRT. The result showed that all ewe ovarian in local pseudo pregnant rabbits post-transplanted were still alive until the fifth or the seventh day of transplantation. Based on the observation and statistic test, in days 5 and 7, it was found a similar status (p<0.05) of post-transplanted ewe ovarian in local and control. The percentages of NZW5 (58.82) COCs decreased significantly (p<0.05) compared to the control (50.36), NZW7 (47.52), local5 (50.42) and local7 (44.78) respectively. It can be concluded that intrauterine transplantation of ewe ovarian to the local and NZW pseudo pregnant rabbits can preserve the ovaries.Key words: ovaries, transplantation, local rabbit, COCs